Continuous Quality Improvement Processes in Child Protection: A Systematic Literature Review. (May 2019) - Zuchowski, Ines; Miles, Debra; Woods, Cindy; Tsey, Komla
Purpose: Protecting children from mistreatment is a global concern, and further research and evaluation in child protection services is required. Continuous Quality Improvement (CQI) has demonstrated potential, but to date, there is no systematic review of studies that evaluate the application of CQI in child protection. Method: This systematic literature review examined the application of CQI in child protection services. The review identified published, English-language evaluations of CQI in child protection from 2000 to 2016 and critiqued the characteristics, methodological quality, and reported benefits of the included studies. Results: A search of social science electronic databases identified eight peer-reviewed studies, including six quantitative studies, one mixed-methods study, and one qualitative study. Discussion: The review highlighted that many studies on this topic lack specific validating data, but there is evidence that CQI models have some potential to improve processes for working with children and families by promoting implementation fidelity.